Thermochemical and structural changes in Jatropha curcas seed cake during torrefaction for its use as coal co-firing feedstock - Madanayakea, Buddhike Neminda; Gan, Suyin; Eastwick, Carol; Ng, Hoon Kiat (Elsevier, 2016)
Jatropha curcas seed cake is a viable feedstock for co-firing with coal as it has the advantages of being renewable, carbon-neutral and sourced from a versatile plant. Torrefaction, a mild pyrolysis treatment by heating in a N2 atmosphere, was investigated as a technique to improve the thermochemical properties of the biomass, primarily the HHV (higher heating value). The temperature and holding time were varied in the ranges of 200–300 °C and 0–60 min, respectively, to form a 5-level full-factorial experimental matrix. An optimum envelope of torrefaction parameters was identified in the range of <5 min at >280 °C to >45 min at 220–250 °C under a heating rate of 10 °C/min. This results in an enhancement of the HHV from 24 MJ/kg to more than 27 MJ/kg, which is within the range of coal, while maintaining an energy yield higher than 90%. The relationships between the HHV and the proximate fixed carbon content as well as the elemental CHO content were also investigated. Through 13C NMR (nuclear magnetic resonance) spectroscopy, hemicellulose was determined as the most volatile component, undergoing decomposition before 250 °C while cellulose only degraded fully in the 250–300 °C range and lignin decomposition spanned from 200 °C to beyond 300 °C.